1987
DOI: 10.1002/j.1460-2075.1987.tb02672.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assembly of U1 snRNPs.

Abstract: An efficient system for the in vitro assembly of U1 snRNPs is described. RNA‐protein interactions in a series of U1 snRNA mutants assembled both in vivo and in vitro were studied in order to verify the accuracy of the system. Two discrete protein binding sites are defined by immunoprecipitation with antibodies against different protein components of the U1 snRNP and a newly developed protein sequestering assay. The U1 snRNP‐specific proteins 70K and A require only the 5′‐most stem‐loop structure of U1 snRNA fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
126
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 36 publications
(26 reference statements)
10
126
0
1
Order By: Relevance
“…U6 was present, but at less than 500-fold coverage, because of its lack of a TMG cap. The remaining RNAs were examined for the expected hallmarks of U1 snRNA: complementarity to known 5′ splice sites in C. merolae (GUAAGU) (6), presence of an Sm-binding site, and binding sites for conserved U1 proteins U1-A and U1-70K (28). Eleven RNAs had a potential Sm-binding site and complementarity to the 5′ splice site, and five of these also contained one canonical U1 proteinbinding site, but sequence alignments to U1 sequences from the Rfam database (29) failed to reveal significant sequence similarity.…”
Section: Resultsmentioning
confidence: 99%
“…U6 was present, but at less than 500-fold coverage, because of its lack of a TMG cap. The remaining RNAs were examined for the expected hallmarks of U1 snRNA: complementarity to known 5′ splice sites in C. merolae (GUAAGU) (6), presence of an Sm-binding site, and binding sites for conserved U1 proteins U1-A and U1-70K (28). Eleven RNAs had a potential Sm-binding site and complementarity to the 5′ splice site, and five of these also contained one canonical U1 proteinbinding site, but sequence alignments to U1 sequences from the Rfam database (29) failed to reveal significant sequence similarity.…”
Section: Resultsmentioning
confidence: 99%
“…protein makes contacts with Ul snRNA at the first stem-loop (20,41) in a sequence-specific manner (46,56). The carboxyterminal portion of the protein is particularly rich in arginine residues and contains repetitions of arginine-glutamic acid, arginine-aspartic acid, and arginine-serine.…”
mentioning
confidence: 99%
“…Previous studies of the RNA-binding properties of the Ul snRNP-specific proteins have involved indirect methods including immunoprecipitation of nuclease-treated cell extracts (34) and microinjection of RNA into Xenopus oocytes (12). These studies suggested that the 70K protein, as well as the A protein and perhaps the C protein, associates with the 5' half of Ul RNA, in particular, stem-loop I.…”
mentioning
confidence: 99%